Safety Guideline: Neurological Monitoring Associated With Obstetric Neuraxial Block 2020 A Joint Guideline by the Association of Anaesthetists and the Obstetric Anaesthetists' Association. Issue 2 (24th June 2021) - Yentis, S.M.; Lucas, D.N.; Brigante, L.; Collis, R.; Cowley, P.; Denning, S.; Fawcett, W.J.; Gibson, A.
Abstract : ( Anaesthesia . 2020;75:913–919) Early detection of neurological complications following a neuraxial procedure is essential to minimizing harm. Previous guidelines for management of neuraxial anesthesia lack guidance on neurological monitoring or are not specific to obstetric patients. The recommendations in this paper were produced by representatives from the Association of Anesthetists and Obstetric Anesthetists' Association with the goal to guide monitoring and management of neurologic recovery in obstetric patients following neuraxial block.